Implikasi Globalisasi dan Kapitalisme Perspektif Teori Dependensi - Nandani Zahara Mahfuzah; Zulkifli Nasution; Fauziah Lubis (Universitas Muhammadiyah Surabaya, 2024)
The purpose of this research is to find out the Implications of Globalization and Capitalism from the Perspective of Dependency Theory. Developing countries will increasingly depend on developed countries in economic, political, and social terms. Literature Review research method is one of the approaches in qualitative research in which researchers conduct analysis in the library by collecting books, documents, archives, and other data sources. Thus, while the IMF plays an important role in regulating globalization, capitalism, and dependency theory in Indonesia, it is also necessary to examine and critique its impact and sustainability in relation to the economic and social interests of various layers of society in Indonesia. The research results of this study show that globalization has significantly impacted market dynamics, integrated the global economy, and strengthened the influence of capitalism and the important role of the legal system in facing the challenges of globalization, capitalism, and dependency theory to create a fair and sustainable regulatory framework.